MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS MULTIPLE INTELLIGENCES (MI) - Hanifudin (EL-Islam, 2021)
This study aims to produce the formulation of the PAI learning model based on multiple intelligences. There are two stages that must be carried out in the application of the multiple intelligences learning models in order to obtain optimal results, namely: (1) empowering all types of intelligence that exist in each subject and (2) optimizing the achievement of certain subjects based on the intelligence that stands out in each. student. This study uses the type of development research (R&D). This study follows Plomp's educational development model which takes five stages, namely: the investigation stage; design stage; construction/realization stage; test/evaluation/revision stage; and implementation stage. The selection of the Plomp model is based on the consideration that; First, this model provides a relatively simple path to get a quality model. Second, this model does not require an experimental-based product test to determine the quality of the model, but it is sufficient to test the model. Based on the research problem formulation, data exposure and analysis, as well as discussion, the results of this study can be concluded as follows: The multiple intelligence-based PAI learning model is a learning model concept whose orientation and purpose is not only to develop and stimulate multiple intelligences that exist in each student, but more than that is an effort to form students who have a harmonious, harmonious, and balanced identity, character, personality in their relationship with Allah SWT, themselves, fellow humans, other creatures, and nature.